Leading Virtual Teams : Hold People Accountable, Build Trust, Encourage Collaboration - Harvard Business Review Press (Boston: HBR Press, 2016)
Whether you have one team member abroad or several people working remotely, leading a virtual team presents special challenges. How do you ensure accountability when you don't see your people every day? How can you get your team to communicate effectively when they're navigating language barriers and time differences and relegated to communication channels, such as email and instant messaging, that invite misinterpretation? Leading an effective virtual team is possible--and this book will give you quick tips and strategies for managing your team productively, no matter how far flung its members might be. Leading Virtual Teams guides you through the basics of: Assessing your team's technological needs Ensuring your team has the right mix of skills and abilities Clarifying the processes, goals, and tools you'll use to communicate and collaborate with your team Keeping your people motivated and engaged--and accountable Navigating common challenges, such as technology glitches, isolation, conflict, and performance issues.--
What is a virtual team? -- Why use virtual teams? -- What are the key challenges? -- Get the right people on the team -- What's important on a virtual team? -- Tweak an existing team -- Assemble a new team -- Manage the technology -- Assess needs and resources -- Seek input -- Set up a team site -- Establish rules for technology use -- What to do when technology fails -- Get to work -- Launch the team -- Create a shared vision -- Define common expectations -- Align priorities -- Build rapport and trust -- Keep people engaged -- Communicate effectively -- Pick the right channel -- Work around time zones and linguistic and cultural barriers -- Avoid communication fatigue -- Find the right balance -- Cope with common problems -- Evaluating performance from a distance -- Maintaining accountability from afar -- Managing conflict on a virtual team.
Includes index.
Keywords: Virtual work teams -- Management; Business communication; Telecommuting